The Pandemic and Parental Mental Health: A Conceptual Review of Parental Burnout - Nurillah, Addiena Hafidza; Herdiana, Ike (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Working from home and schooling from home activities are widely reported to have an impact on parental burnout in parents due to the burden of care that arises when implementing policies to carry out all activities from home during the COVID-19 pandemic. Even though work and school activities have now returned to institutional buildings, it does not rule out the possibility that a pandemic situation will reappear in the future. Hence parents need to learn how to anticipate it. This article aims to provide an overview of the concept of parental burnout which has become a research trend on the theme of families during the pandemic. A search was carried out on the electronic databases namely Web of Science, Google Scholar, and ScienceDirect with the keyword